2016
DOI: 10.4103/2231-0746.186143
|View full text |Cite
|
Sign up to set email alerts
|

Success rate of implants placed in autogenous bone blocks versus allogenic bone blocks: A systematic literature review

Abstract: The aim of this study is to review and compare survival/success rate of dental implants inserted in autogenous and allogenic bone blocks (ALBs). A PubMed search was performed from January 1990 to June 2014 limited to English language and human studies. Studies that reported treatment outcome of implants inserted in augmented alveolar ridges with autogenous or ALBs were included. Primary search identified 470 studies. For autogenous bone block (ABB) 36 articles and for ALB 23 articles met the inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 69 publications
(326 reference statements)
2
30
0
1
Order By: Relevance
“…The success rate of the block grafts was very effective and comparable with those reported by other authors [37][38][39]. Besides, the augmentation procedure permitted the insertion of implants in the grafted area 9 months after surgery.…”
Section: Discussionsupporting
confidence: 85%
“…The success rate of the block grafts was very effective and comparable with those reported by other authors [37][38][39]. Besides, the augmentation procedure permitted the insertion of implants in the grafted area 9 months after surgery.…”
Section: Discussionsupporting
confidence: 85%
“…However, the use of this material has disadvantages: the need for an additional surgical site, the more invasive procedure, the quantitative limit of bone that can be harvested from the donor site, and the morbidity for the patient [4, 16, 30]. For this reason, different materials have been proposed as possible alternatives, such as allografts [31] and xenografts [32]. Although both allografts and xenografts have been extensively used in bone reconstruction procedures [31, 32], the use of these materials will probably be restricted in future, because they may carry the risk of disease transmission: the processes for their preparation and sterilization might not totally exclude the presence of active viruses or prions [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, different materials have been proposed as possible alternatives, such as allografts [31] and xenografts [32]. Although both allografts and xenografts have been extensively used in bone reconstruction procedures [31, 32], the use of these materials will probably be restricted in future, because they may carry the risk of disease transmission: the processes for their preparation and sterilization might not totally exclude the presence of active viruses or prions [33, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown relatively high success rate of dental implants. [ 17 23 ] To keep the implant healthy and functional, periodic follow-ups are necessary. During these follow-ups, clinical and radiographic examinations should be performed which would reveal valuable information comparable to the histologic evaluations.…”
Section: Discussionmentioning
confidence: 99%